2016
DOI: 10.3390/ijms17040518
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Hyperglycemia Induced Endothelial Cell Dysfunction

Abstract: Hyperglycemia is closely associated with prediabetes and Type 2 Diabetes Mellitus. Hyperglycemia increases the risk of vascular complications such as diabetic retinopathy, diabetic nephropathy, peripheral vascular disease and cerebro/cardiovascular diseases. Under hyperglycemic conditions, the endothelial cells become dysfunctional. In this study, we investigated the miRNA expression changes in human umbilical vein endothelial cells exposed to different glucose concentrations (5, 10, 25 and 40 mM glucose) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 141 publications
2
50
0
3
Order By: Relevance
“…miR-29b may thus also be a vital inflammatory marker that plays an important role in the development of subclinical or clinical atherosclerosis. miR-29b has also been reported to be associated with endothelial cell dysfunction [18]. Mott et al [19] reported that miR-29b is an important endogenous regulator, which plays a role in endothelial cell apoptosis by inhibiting the anti-apoptotic gene, myeloid cell leukemia-1.…”
Section: Discussionmentioning
confidence: 99%
“…miR-29b may thus also be a vital inflammatory marker that plays an important role in the development of subclinical or clinical atherosclerosis. miR-29b has also been reported to be associated with endothelial cell dysfunction [18]. Mott et al [19] reported that miR-29b is an important endogenous regulator, which plays a role in endothelial cell apoptosis by inhibiting the anti-apoptotic gene, myeloid cell leukemia-1.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is a systemic metabolic condition, and the animal model of STZ-induced diabetes is characterized by disruption of pancreatic beta-cells, which cannot release insulin, leading to hyperglycaemia (Szkudelski, 2001). The overlap between serum and retinal expression of the focused set of dysregulated miRNAs in STZ diabetic mice would suggest that hyperglycaemia modifies miRNA expression at a systemic level (Ocłoń, Latacz, Zubel-Łojek, & Pierzchala-Koziec, 2016;Silambarasan et al, 2016;Simionescu et al, 2016). Moreover, circulating miRNAs could come from exosomes, released from several tissues, working as paracrine signalling molecules in hyperglycaemic conditions (Guay & Regazzi, 2013;Gupta, Bang, & Thum, 2010;Hashimoto & Tanaka, 2017).…”
Section: Bdnf Ppar-α Creb1 and Vegf Dysregulation In Diabetic Rementioning
confidence: 99%
“…The authors found that miR-29b was not dysregulated in type 2 diabetes in the subgroup analyses of miRNAs in circulating blood and in human profiling studies. 14 However, these findings contrast with studies that reported either higher circulating levels of miR-29 in subjects with prediabetes 37 and type 2 diabetes 35,37 or lower miR-29b levels in those with prediabetes 38 and who developed type 2 diabetes in the prospective population-based Bruneck study. 39 It is tempting to speculate whether miR-29b is up-regulated in type 2 diabetes as a failed attempt to compensate for the endothelial dysfunction, as 27 The authors showed that miR-29 is required for normal endothelial function and can restore it in cardiometabolic disorders.…”
Section: Discussionmentioning
confidence: 88%